Nitrogen fertilization of coffee tree with jack-bean biomass - Araújo, João Batista Silva; Rodrigues, Luisa Bastos; Rodrigues, Mateus Cupertino; Martinez, Hermínia Emilia Prieto; Santos, Ricardo Henrique Silva (Coffee Science - ISSN 1984-3909, 2014)
The aim of this study was to evaluate the growth and production of coffee tree and transfer of N from biomass legumes to coffee tree cropping without the interference of field consortium. Coffee trees were cultivated in pots, and after shoots of jack bean, enriched with 15N into the pots in greenhouse, at doses of 146 and 584 g plant-1, supplemented with 30% of mineral fertilizer. Jack-bean promotes increases coffee yield, the best index of soil quality (concentration of Ca2+, sum of bases, effective CEC, soil organic matter). Foliar N content derived from jack-bean, five months after fertilization, were 4.68% and 18.65% at the respective doses of 146 and 584 g plant-1. The percentage of N derived from jack bean in coffee leaves is proportional to the applied dose.